PENGARUH PEMBERIAN JUS BAYAM MERAH (AMARANTHUS GANGETICUS) TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL PENDERITA ANEMIA DI KLINIK SALMA KEC.PERBAUNGAN TAHUN 2020 - Keleng Ate Ginting; Raini Panjaitan; Andreais Boffil Cholilullah; Anggi Isnani Parinduri; Resty Tri Yanti (JURNAL KESMAS DAN GIZI (JKG), 2021)
Anemia in pregnant women greatly affects iron deficiency, because in pregnancy the need for oxygen is higher, which triggers an increase in erythropoietin production (Cunninggham, 2016). (WHO, 2010), globally the prevalence of anemia in pregnant women worldwide is 41.8%. The prevalence of anemia in pregnant women in Indonesia increased compared to 2013, in 2013 as many as 37.1% of pregnant women were anemic while in 2018 it increased to 48.9% (Riskesdas, 2018). One alternative to meet iron needs can be done by consuming vegetables, one of which is red spinach. The aim is to determine the effect of giving red spinach juice on increasing hemoglobin levels in pregnant women with anemia at the Salma Clinic, Perbaungan district in 2020. The method of pre-experimental research was one group pretest-posttest study design. The population in this study were all 28 pregnant women. January to May 2020. Sampling using purposive sampling technique. To determine the differences in the production of Hb levels before and after intervention in pregnant women and Hb Check. The statistical test used in this study was the paired sample T-Test, if the p value was â‰¤ 0.05. The results of the analysis test using paired sample t-test in the experimental group obtained a value of p = 0.025 <(Î± = 0.05), it can be concluded that the hypothesis in this study was accepted, namely the effect of giving red spinach juice on pregnant women with anemia at the Salmah Perbaungan Clinic, Serdang Bedagai Regency